2017
DOI: 10.17957/ijab/15.0340
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic, Transcriptomic and Metabolomic Expression Analysis of Aroma Gene (badh2) under Different Temperature Regimes in Rice

Abstract: To cite this paper: Prodhan, Z.H., G. Faruq, R.M. ) and grain yield per plant (76.73 g) were higher at 25°C temperature compared to the ambient and 20°C temperature. The maximum down-regulation of badh2 gene (-12.20 ± 0.01 fold), the highest concentration of 2AP (0.14 ± 0.02 ppm) and the excellent phenotypic aroma score (score 4) was also observed at 25°C temperature. Hence, the badh2 gene expression level and 2AP concentration were influenced by the temperature, which also regulated the phenotypic expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…This result is in agreement with Ocan et al (2019) who also found differences in the strength of aroma among aromatic rice varieties. The strength of aroma is known to be influenced by cultivation condition such as temperature (Prodhan et al, 2017), Light intensity (Mo et al, 2015), plant nutrition (Lei et al, 2018) Figure 1. Sequence analysis showing the presence or absence of the 8bp deletion and three SNPs on exon two of the badh2 gene in selected accessions.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with Ocan et al (2019) who also found differences in the strength of aroma among aromatic rice varieties. The strength of aroma is known to be influenced by cultivation condition such as temperature (Prodhan et al, 2017), Light intensity (Mo et al, 2015), plant nutrition (Lei et al, 2018) Figure 1. Sequence analysis showing the presence or absence of the 8bp deletion and three SNPs on exon two of the badh2 gene in selected accessions.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of foliage dressing with proline on grain yield, brown rice rate, milled rice rate, head rice rate, protein content, amylose content, chalky rice rate and chalkiness. The means in the same column followed by different lowercase letters for the same variety differ significantly at P < 0.05. www.nature.com/scientificreports/ and the down-regulation in BADH2′s transcript level and BADH activity could be other important reason for the increased grain 2-AP concentration 22,23 . Interestingly, we observed that exogenous proline also improved some other grain quality attributes of fragrant rice.…”
Section: Discussionmentioning
confidence: 99%
“…We deduced that the increased proline concentration induced the up-regulation in both ProDH activity and transcript level of PRODH and thus promoted the transformation from proline to P5C to △1-pyrroline and then to 2-AP 20 , 21 . On the other hand, as the key aroma gene in fragrant rice, the change in gene BADH2 expression cannot be neglected and the down-regulation in BADH2 ′s transcript level and BADH activity could be other important reason for the increased grain 2-AP concentration 22 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Shan et al (2015) reported the creation of fragrant rice (with high 2AP content) from a nonaromatic variety by using gene editing technologies, sequence-specific nucleases and transcription activator-like effector nucleases. Despite, the significant influence of genetics on rice grain aroma, several other factors are known to contribute towards the aromatic profile of rice, and the intensity, for example soil salinity (Poonlaphdecha et al, 2012), plant nutrition (Lei et al, 2017), agronomic practices (Goufo et al, 2010), light intensity (Mo et al, 2017) and temperature (Prodhan et al, 2017). The concentration of other biological compounds such as 1-pyrroline has been directly implicated in the biosynthesis of 2AP (Prodhan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%